Critical evaluation of thin film composite membrane for pesticide removal - Lee, Shirley Sze Ying (2021)
Pesticides are widely used by farmers in the agricultural field to control the proliferation of pests growth to achieve higher yield of crops. However, high level of these pesticides cause negative effects on the environment and wellbeing of living organisms. Membrane separation is an efficient way to remove both pesticides and other micropollutants in wastewater. This study presents a critical evaluation of thin film composite membranes on pesticides removal. Different types of processes using thin film composite membranes discussed were nanofiltration (NF), reverse osmosis (RO) and forward osmosis (FO) (i.e. FO mode and pressure retarded osmosis (PRO) mode) processes. This paper mainly focuses on how certain parameters such as operating pressure, system configuration, pesticide characteristics, membrane characteristics, feed solution and draw solution affect the performance of the membrane. The effects of these parameters on pesticides rejection and permeate flux are studied by comparing the results and findings obtained from various literatures to conclude on the optimum operating conditions for the membranes to achieve high removal efficiency. It was found that the effects of the parameters mentioned varies according to the type of membranes. Generally, high pressure showed positive effects on NF and RO membranes flux performances but could deform PRO membranes. In terms of system configuration, cross-flow configuration in the pressure-driven membranes and FO mode are desired. Besides, hydrophobic pesticides that are larger in size, negatively charged with small dipole moments showed higher retention. The intensity of membrane fouling which reduces membrane performance can be affiliated to its materials. Humic acid has a positive effect on membrane fouling. Ions in the feed solution increased the rejection efficiency and permeate flux of membrane whereas pesticides concentration has a negative effect on their retention. pH of feed solution determines the zeta potential of membrane. As for the draw solution, NaCl at higher concentration is recommended. Thus, it can be concluded that membrane processes are among the prominent approaches to reduce pesticides levels in agricultural wastewater to below the legal standard of pesticides in drinking water set by WHO.